PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS INKUIRI TERBIMBING PADA MATERI GARAM HIDROLISIS - Venny Ferli Yanti; Ila Rosilawati; Tasviri Efkar (Universitas Lampung, 2016)
The research and development was aimed to develop and describe validity, practicality, and effectiveness of student worksheets based guided inquiry on content salt hydrolysis. Validation gave an assessment to the aspects of construction, readability, suitability of content of worksheets in high category and the worksheets was declared valid. Teacher feedback on aspects of the suitability of the content, readability, the attractiveness of the worksheets were very high categorized; student responses to aspects of legibility and attractiveness was very high categorized; students' response positive of the learning to use the worksheets; and the results of observation by using the worksheets was very high categorized. The worksheets was said practically to the used.Penelitian dan pengembangan ini bertujuan untuk mengembangkan dan mendeskripsikan kevalidan, kepraktisan, serta keefektifan lembar kerja siswa berbasis inkuiri terbimbing pada materi garam hidrolisis. Validator memberikan penilaian pada aspek konstruksi, keterbacaan, kesesuaian isi LKS dikatagorikan tinggi dan LKS dinyatakan valid. Tanggapan guru pada aspek kesesuaian isi, keterbacaan, kemenarikan LKS dikategorikan sangat tinggi; tanggapan siswa terhadap aspek keterbacaan dan kemenarikan dikatagorikan sangat tinggi respon siswa terhadap pembelajaran menggunakan LKS positif dan hasil observasi pembelajaran menggunakan LKS dikategorikan sangat tinggi. LKS dapat dikatakan praktis untuk digunakan.Kata kunci : lembar kerja siswa, inkuiri terbimbing, garam hidrolisis